Draft Annual Plan 1972-73 Government of the Union Territory Goa, Daman and Diu - Planning Commission (Planning Commission, 1972)
Since liberation first time attempt was made to calculate the Regional Income of this territory. Total income for the year 1967-68 amounted to Rs.46.26 crores and for 1968-69 amounted to Rs.48.10 crores. Per Capita Incomes was Rs.6941 and Rs.715 for the year 1967-68, 1968-69,respectively. The figures are based on the population worked out on the basis of the quinquennial estimates of population (period 1966-1971) as supplied by the Planning Commission. It would be seen that just prior to liberation the Regional Income of the Territory was 27.18 crores and the per capita income was RS.434/-.
Government of the Union Territory Goa, Daman and Diu, Planning Department